Investigation of possibilities for astronomical meridian determination by the hour angle of the Sun - Petras Petroškevičius (Geodesy and Cartography, 2012)
Results of investigation of the astronomical meridian determination possibilities are presented in the paper. For defining the meridian direction the method of astronomical azimuth determination by the hour angle of the Sun is analysed. Best conditions for the Sun’s azimuth determination were investigated. Effect of points and the Sun’s coordinate errors were analysed. Relation of hour angle of the Sun error effect on the Sun declination and latitude was determined. Possibilities for the latitude and declination errors effect reduction are specified. Special features for horizontal angle between selected direction and the Sun observation are analysed. Effect of the Sun’s visual radius and azimuth change acceleration was analysed. Based on the obtained results, it is possible to select an optimal time for determining the astronomical azimuth of direction as well as for determining the direction of astronomical meridian, depending on known parameters errors, point latitude and season.